2013
DOI: 10.1002/2013ja018872
|View full text |Cite
|
Sign up to set email alerts
|

Full halo coronal mass ejections: Do we need to correct the projection effect in terms of velocity?

Abstract: [1] The projection effect is one of the biggest obstacles in learning the real properties of coronal mass ejections (CMEs) and forecasting their geoeffectiveness. To evaluate the projection effect, 86 full halo CMEs (FHCMEs) listed in the Coordinated Data Analysis Workshop CME catalog from 1 March 2007 to 31 May 2012 are investigated. By applying the Graduated Cylindrical Shell model, we obtain the deprojected values of the propagation velocity, direction, and angular width of these FHCMEs and compare them wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 76 publications
7
54
3
Order By: Relevance
“…Our results are almost similar to Michalek (2010), who evaluated an average width for 69 halo CMEs from 2001 and 2002 by applying an asymmetric cone model to SOHO/ LASCO data. The mean value (100°) of the 3D widths for the full halo CMEs is quite similar to Shen et al (2013), who showed that the average value of the 3D widths from the GCS model is 103°. Figure 4 shows the yearly variation of CME speed together with the yearly sunspot number, indicating solar activities.…”
Section: Methodssupporting
confidence: 82%
See 4 more Smart Citations
“…Our results are almost similar to Michalek (2010), who evaluated an average width for 69 halo CMEs from 2001 and 2002 by applying an asymmetric cone model to SOHO/ LASCO data. The mean value (100°) of the 3D widths for the full halo CMEs is quite similar to Shen et al (2013), who showed that the average value of the 3D widths from the GCS model is 103°. Figure 4 shows the yearly variation of CME speed together with the yearly sunspot number, indicating solar activities.…”
Section: Methodssupporting
confidence: 82%
“…This indicates that most CMEs propagate radially to some extent, although some CMEs are noticeably deflected. Furthermore, we compare our findings with those of Shen et al (2013) using 34 overlapping events in Figure 8. All parameters are similar to each other, with higher correlation (0.75).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations